Power over people classical and modern political theory - Dalton, Dennis; Teaching Company (Springfield, VA Teaching Co., 1996)
Presents lectures on the philosophical concepts of political science.
pt. 1: lecture 1. The Hindu vision of life ; lecture 2. Thucydides and the Peloponnesian war ; lecture 3. Law and rule in Sophocles' Antigone ; lecture 4. Socrates and socratic quest ; lecture 5. Plato, idealism and power : part 1 ; lecture 6. Plato, idealism and power : part 2 ; lecture 7. Aristotle's critique of Plato's Republic ; lecture 8. Machiavelli's theory of power and politics -- pt. 2: lecture 9. Rousseau's theory of human nature and society ; lecture 10. Marx's critique of capitalism and solution of communism ; lecture 11. Freud's theory of human nature and civilization ; lecture 12. Thoreau's theory of civil disobedience ; lecture 13. Dostoevsky's grand inquisitor ; lecture 14. The idea of anarchism and the example of Emma Goldman ; lecture 15. Hitler's use of power ; lecture 16. Gandhi's use of power.
Teaching Co.: 441A--442A.
In two containers (26 cm.).
Keywords: Political science -- Philosophy